TEACHERS’ PERCEPTION IN USING TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN TEACHING ENGLISH AT SENIOR HIGH SCHOOLS IN BULELENG SUB-DISTRICT - Prasetya, I.W.A.W; Putra, I.N.A.J.; Budasi, I.G. (Language and Education Journal Undiksha, 2019)
This study is aimed at investigating English teachers' perception in using Technological Pedagogical Content Knowledge (TPACK) framework in teaching and learning process at Senior High schools in Buleleng Sub District. This study applied an explanatory sequential mixed method design which used a questionnaire and interview guide as the instruments that had been tested for their validity and reliability. The data from the questionnaires were processed by using a Microsoft Office Excel to calculate the mean score in order to know the qualification level of each the dimension. The results of data analysis showed that most of the teachers had positive perceptions of using TPACK framework in teaching English at senior high schools. It was shown by the position of mean score in the high position of the interval with the mean score was 139.074.